المستشرق أرنولد جوزيف توينبي و آرائه حول الإسلام في ضوء كتابه "مختصر دراسة للتاريخ: Orientalist Arnold Joseph Toynbee and his vision about Islam in the light of his book “Abridgment A Study of History” (An Analytical and Critical Study) - muzfar, Dr. Muzfar Ali; Dr. Abdul Rehman Hammad (MEI, 2023)
Arnold Joseph Toynbee was a renowned British historian and philosopher who played a significant role in shaping the Western perception of the Muslim world. His work, "A Study of History," is a monumental project that attempts to provide a comprehensive analysis of the entire history of humanity. However, Toynbee's views on Islam have been subject to criticism, particularly from scholars who have challenged his Orientalist perspective. This research article analyzes the Orientalist perspective of Arnold Joseph Toynbee on Islam and its impact on his book "A Study of History." The paper offers an analytical and critical study of Toynbee's vision, which portrays Islam as an "incomplete civilization." The article delves into the historical context and philosophical assumptions that shaped Toynbee's ideas and examines how his beliefs on Islam and the Muslim world influenced his interpretation of history. The paper highlights the problematic nature of Toynbee's Orientalist lens and argues that his understanding of Islam is reductive and essentialist. Ultimately, the article seeks to challenge Toynbee's portrayal of Islam and to provide a more nuanced and complex understanding of the religion and its place in history.